Simple Tools to Assist in the Resolution of Troubled Banks - McGuire, Claire L. (World Bank, Washington, DC, 2013)
This toolkit is designed to assist authorities in resolving troubled banks. It provides generic forms that can be adapted for use in planning supervisory actions or implementing resolution processes. This toolkit contains forms that are generic and will need to be tailored to the particular country laws and circumstances. The toolkit also contains a least cost or lesser cost model and explanatory guide that provide diagnostic tools to assist authorities in estimating the costs of various resolution methods. The least cost or lesser cost model can also be used to value various assets that may be offered for sale as part of the resolution process. In some circumstances, the decision will be made to liquidate a bank at the end of a long period of utilizing other supervisory tools to try to rehabilitate the bank, thereby providing the authorities with adequate time to gather information about the problem bank and prepare a plan for its closure. In other circumstances, the authorities will have little time to plan for a bank's closing and will have to rely on their general crisis preparedness tools to handle the resolution process as efficiently as possible. Whichever circumstances are present, planning for bank resolution should be part of a country's overall strategy for its financial sector.